Transgene Pyramiding of Salt Responsive Protein 3-1 (SaSRP3-1) and SaVHAc1 From Spartina alterniflora L. Enhances Salt Tolerance in Rice - Biradar, Hanamareddy; Karan, Ratna; Subudhi, Prasanta K. (Frontiers in Plant Science, 2018)
The transgenic technology using a single gene has been widely used for crop improvement. But the transgenic pyramiding of multiple genes, a promising alternative especially for enhancing complexly inherited abiotic stress tolerance, has received little attention. Here, we developed and evaluated transgenic rice lines with a single Salt Responsive Protein 3-1 (SaSRP3-1) gene as well as pyramids with two-genes SaSRP3-1 and Vacuolar H+-ATPase subunit c1 (SaVHAc1) derived from a halophyte grass Spartina alterniflora L. for salt tolerance at seedling, vegetative, and reproductive stages. The overexpression of this novel gene SaSRP3-1 resulted in significantly better growth of E. coli with the recombinant plasmid under 600 mM NaCl stress condition compared with the control. During early seedling and vegetative stages, the single gene and pyramided transgenic rice plants showed enhanced tolerance to salt stress with minimal wilting and drying symptoms, improved shoot and root growth, and significantly higher chlorophyll content, relative water content, and K+/Na+ ratio than the control plants. The salt stress screening during reproductive stage revealed that the transgenic plants with single gene and pyramids had better grain filling, whereas the pyramided plants showed significantly higher grain yield and higher grain weight compared to control plants. Our study demonstrated transgenic pyramiding as a viable approach to achieve higher level of salt tolerance in crop plants.